Use of Doppler ultrasound as prediction of preeclampsia at the early pregnancy - Sa?söz, Nevin; Bostanci, Mehmet Sühha; Yücel, Aykan; Noyan, D. Volkan (My University, 2007)
Doopler ultrasound may be useful for prediction of preeclampsia by performing with the first or second trimester ultrasound pregnancy screening. This can be increase the patient adjusment and also decrease the cost of the screening. According to the first trimester studies, sensitivity of Doopler ultrasound is lower than second trimester studies. But first trimester Doppler ultrasound give a chance of early prediction and prophylaxis for preeclampsia. However sensitivity and PPV values of first trimester studies must be increase. By the way unuseless drug consumption will be prevented at the normal pregnant population. For increase the sensitivity and PPV values, to profit by serum markers may be helpful. However for routine screening of preeclampsia, Doppler ultasound combination with the serum markers is still limited. For this reason wide longitudinal population studies are neccessary for the use Doopler ultrasound and serum markers as a screening test. There is no cost effectiveness studies about Doopler ultrasound and serum marker combinations which are necessary to perform.
Erken gebelikte preeklampsi gelişimini belirlemede Doppler ultrasonografi
Keywords: biological marker; chorionic gonadotropin; human placenta lactogen; leptin; cost effectiveness analysis; Doppler flowmetry; health care cost; human; preeclampsia; pregnancy; prophylaxis; review; screening; sensitivity and specificity